2017
DOI: 10.1007/s00170-017-0775-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laser heat treatment on microstructure and properties of surface layer of Waspaloy aimed for laser-assisted machining

Abstract: In this study, a nickel-based superalloy, Waspaloy, was laser heat treated with diode laser. Single laser tracks were manufactured with different laser beam power densities between 63 and 331 kW/cm 2 , and scanning laser beam speed ranged from 5 to 100 m/min. It was found that laser heat treatment of Waspaloy causes decrease in material hardness-the microhardness in laser tracks is about 300 HV0,1 while the microhardness of substrate is ranged from 300 to 600 HV0,1-which is a positive phenomenon for laserassis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Methods for improving the surface properties of titanium alloys include electroless plating [4,5], electrodeposition [6], laser cladding [7,8], spray coating [9], air atmosphere treatment [10], laser assisted machining [11,12] and laser heat treatment [13][14][15]. Electrodeposition with a simple process and low cost is commonly used in the preparation of nan materials, composite plating, and special function plating [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Methods for improving the surface properties of titanium alloys include electroless plating [4,5], electrodeposition [6], laser cladding [7,8], spray coating [9], air atmosphere treatment [10], laser assisted machining [11,12] and laser heat treatment [13][14][15]. Electrodeposition with a simple process and low cost is commonly used in the preparation of nan materials, composite plating, and special function plating [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that addition of copper which is the second main element of Monel 400, to boron layer, reduces brittleness and enhances wear resistance of the surface [5,18]. Borided layers are mostly produced in diffusion processes but in the last two decades of intensive laser techniques progress, there was a much increase in using lasers for obtaining boron-alloyed metal surfaces [14,16,17,[19][20][21][22][23][24] and others [25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, diode lasers are characterized by lower maintenance costs and a possibility to deliver a radiation in fiber. These features resulted in raising interest in using diode lasers for metal processing, for example, laser alloying [19-23, 26, 28, 30-33], laser hardening [24,29,34], or laser-assisted machining [27,[34][35][36]. Because of their potential, diode lasers systems are still improved to obtain better beam quality and higher power intensity [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main problem occurs in the correlation of technological parameters on various quality indicators. The improvement of the effects of LAT is related to the area of technological and geometric variable parameters occurring in the cutting process [4][5], laser heating [6][7][8][9] and geometric variables defining the relationship between the place of beam incidence and material decohesion [3,6,9]. Better machinability indicator can be achieved by using two kinematic variations of the laser-assisted machining process: by thermal softening of the heated cutting layer and by changing the microstructure of the surface layer of the workpiece [3].…”
Section: Introductionmentioning
confidence: 99%